Parasitic nematode fatty acid- and retinol-binding proteins compromise host immunity by interfering with host lipid signaling pathways - Sophia C. Parks (Public Library of Science (PLoS), 2021)
Parasitic nematodes cause significant morbidity and mortality globally. Excretory/secretory products (ESPs) such as fatty acid- and retinol- binding proteins (FARs) are hypothesized to suppress host immunity during nematode infection, yet little is known about their interactions with host tissues. Leveraging the insect parasitic nematode, Steinernema carpocapsae, we describe here the first in vivo study demonstrating that FARs modulate animal immunity, causing an increase in susceptibility to bacterial co-infection. Moreover, we show that FARs dampen key components of the fly immune response including the phenoloxidase cascade and antimicrobial peptide (AMP) production. Our data also reveal that FARs deplete lipid signaling precursors in vivo as well as bind to these fatty acids in vitro, suggesting that FARs elicit their immunomodulatory effects by altering the availability of lipid signaling molecules necessary for an efficient immune response. Collectively, these data support a complex role for FARs in immunosuppression in animals and provide detailed mechanistic insight into parasitism in phylum Nematoda. Author summary A central aspect of parasitic nematode success is their ability to modify host biology, including evasion and/or subversion of host immunity. Modulation of host biology and the pathology caused by parasitic nematodes is largely effected through the release of proteins and small molecules. There are hundreds of proteins released by nematodes during an infection and few have been studied in detail. Fatty acid- and retinol-binding proteins (FARs) are a unique protein family, found only in nematodes and some bacteria, and are released during nematode infection. We report that nematode FARs from S. carpocapsae, C. elegans and A. ceylanicum dampen fly immunity decreasing resistance to infection. Mechanistically, this is achieved through modulation of the phenoloxidase cascade and antimicrobial peptide production. Furthermore, FARs alter the availability of lipid immune signaling precursors in vivo and show binding specificity in vitro.